2020
DOI: 10.1111/cns.13535
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing synchronous firing of epileptiform activity by high‐frequency stimulation of afferent fibers in rat hippocampus

Abstract: Aims Deep brain stimulation (DBS) is a promising technology for treating epilepsy. However, the efficacy and underlying mechanisms of the high‐frequency stimulation (HFS) utilized by DBS to suppress epilepsy remain uncertain. Previous studies have shown that HFS can desynchronize the firing of neurons. In this study, we investigated whether the desynchronization effects of HFS can suppress epileptiform events. Methods HFS trains with seconds of duration (short) and a minute of duration (long) were applied at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The positions of electrodes were kept fixed throughout the period of data collection. After the animal experiments, the correction of electrode positions was confirmed by a histology analysis of brain slices ( Wang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The positions of electrodes were kept fixed throughout the period of data collection. After the animal experiments, the correction of electrode positions was confirmed by a histology analysis of brain slices ( Wang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, optogenetic inhibition of principal excitatory CA3 neurons using Jaws in the PP kindling model significantly reduced afterdischarge duration and behavioral severity 31 . Additionally, in an anesthetized rat model of afterdischarge (SC stimulation), high‐frequency electrical stimulation of the SC prevented afterdischarge propagation to the CA1 subfield by desynchronizing neurons from epileptiform activity 47 . Several studies have indicated the potent seizure‐suppressing effects of activating GABAergic interneurons (i.e., indirectly inhibiting excitatory neurons) in various preclinical models.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Additionally, in an anesthetized rat model of afterdischarge (SC stimulation), high‐frequency electrical stimulation of the SC prevented afterdischarge propagation to the CA1 subfield by desynchronizing neurons from epileptiform activity. 47 Several studies have indicated the potent seizure‐suppressing effects of activating GABAergic interneurons (i.e., indirectly inhibiting excitatory neurons) in various preclinical models. However, depending on the interneuronal axonal projections, such an optogenetic inhibitory approach can affect larger volumes of the brain beyond the illuminated site.…”
Section: Discussionmentioning
confidence: 99%
“…Then the SE was inserted gradually to approach the alveus until the amplitude of APS evoked by a test cathodicpulse (100 µs, 0.3 or 0.4 mA) was not able to increase further, indicating that the inner pole of SE had reached the alveus. After the experiments, the electrode positions were confirmed by stained sections (figure 1(A, right)) of paraformaldehyde-fixed brains by histological methods reported previously [28].…”
Section: Animal Surgery and Electrode Implantationsmentioning
confidence: 99%